Anatomic Description of the Ulna of the White-Footed Tamarin (Saguinus leucopus Günther, 1876) - Vélez-García,Juan Fernando (Sociedad Chilena de Anatomía, 2016)
This document is a description of the macroscopic functional anatomy of the ulna bony prominences in the White-footed Tamarin (Saguinus leucopus), a neotropical endemic, and monotypic primate of Colombia. Few studies have been conducted on its anatomy, and thus its ulnar morphology, an essential element for this animal's quadrupedal arboreal locomotion, remains unknown. This study is based on eight specimens, fixed in formalin at 10 % whose ulnas were extracted in order to describe the main bony prominences along with muscular and ligamentous fixation functions. These elements of the locomotor apparatus and the multiple anatomical contours of the ulna of the White-footed Tamarin, exhibit characteristics for positional and articular adjustment with other bones of the forelimb in harmony with the attachments of the muscles, essential for quadrupedal arboreal locomotion.